Pengaruh Media Loose Part Terhadap Kemampuan Berhitung Anak Usia 4-5 Tahun di TK - Rahmadani; Icam Sutisna; Pauweni, Apriyanto A.J (Student Journal of Early Childhood Education, 2024)
This study aimed to determine the effect of loose part media on the counting skills of 4-5-year-old at TK State Menara Laut Kindergarten, Leato District, Gorontalo City. This study employed a quantitative experimental method with a one-group pretest-posttest design on 15 children from Group A at the mentioned Kindergarten. The pretest data showed a highest score of 16 and a lowest score of 12, with an average score of 14.27. On the other hand, the posttest data displayed a highest score of 30 and a lowest score of 25, with an average score of 28.07, indicating an increase in the average score of 13.80. The results were also supported by the hypothesis test (t-test), showing a calculated t-count of 37.53 and a t-table of 2.14. This indicates that the t-count was greater than the t-table (37.53 > 2.14). Therefore, it was concluded that Ho was rejected, and H1 was accepted. This meant that there was a significant influence of the loose parts media on the counting skills of children at TK State Menara Laut Kindergarten in Leato District, Gorontalo City. Thus, the use of loose parts media proved to be an effective learning strategy for improving early childhood counting skills.